Lifetime Drinking Trajectories and Nonfatal Acute Myocardial Infarction. (30th September 2019) - Russell, Marcia; Fan, Amy Z.; Freudenheim, Jo L.; Dorn, Joan; Trevisan, Maurizio
Abstract : Background: The relation of lifetime drinking trajectories to coronary heart disease is not well understood. Methods: Cases hospitalized for a nonfatal acute myocardial infarction (AMI) and healthy population‐based controls matched on age and sex completed a physical examination and an interview covering known AMI risk factors and a detailed lifetime drinking history. Distinct lifetime drinking trajectories based on ounces of ethanol consumed per decade between ages 10 and 59 years were derived and characterized according to lifetime drinking patterns associated with each. Sex‐specific multiple logistic regression analyses were conducted to estimate AMI risk among participants who never drank regularly compared to lifetime drinking trajectories and risk associated with distinct trajectories among former and current drinkers. Results: Two lifetime drinking trajectories were derived, early peak and stable. Early peak trajectories were characterized by earlier onset of regular drinking, less frequent drinking, more drinks per drinking day, fewer total drinks, more frequent drunkenness per drinking year, and reduced alcohol intake or abstention by middle age. Never drinking regularly, reported by significantly more women than men, was associated with significantly higher AMI risk than stable lifetime drinking trajectories among men and in the sex‐combined analysis of former drinkers only. Compared to stable lifetime drinking trajectories, early peak trajectories were associated with significantly higher AMI risk among male former drinkers, among sex‐combined former drinkers, and among female current drinkers. Conclusions: Epidemiological studies of alcohol and health in populations over age 35 may have underestimated the impact of heavy episodic drinking during adolescence and emerging adulthood on the cardiovascular system. Abstract : A retrospective case‐control study indicated, for the first time, that increased risk of heart attack is associated with early peak lifetime drinking trajectories, characterized by early drinking onset, harmful drinking patterns, and reduced drinking or abstention by middle age. Accordingly, the impact of early heavy drinking on the initiation and progression of cardiovascular disease may be underestimated in previous studies of older populations.